Visual reading for [18F]Florzolotau ([18F]APN-1607) tau PET imaging in clinical assessment of Alzheimer’s disease - Lin, Huan-Chun; Lin, Kun-Ju; Huang, Kuo-Lun; Chen, Shih-Hsin; Ho, Tsung-Ying; Huang, Chin-Chang; Hsu, Jung-Lung; Chang, Chiung-Chih; Hsiao, Ing-Tsung (Frontiers in Neuroscience, 2023)
Introduction Tau-targeted positron emission tomography (tau-PET) is a potential tool for the differential diagnosis of Alzheimer’s disease (AD) and to clarify the distribution of tau deposition. In addition to the quantitative analysis of tau-PET scans, visual reading supports the assessment of tau loading for clinical diagnosis. This study aimed to propose a method for visually interpreting tau-PET using the [18F] Florzolotau tracer and investigate the performance and utility of the visual reading. Materials and methods A total number of 46 individuals with 12 cognitively unimpaired subjects (CU), 20 AD patients with mild cognitive impairment (AD-MCI), and 14 AD with dementia (AD-D) patients with both [18F]Florbetapir amyloid PET and [18F]Florzolotau tau PET scans were included. Clinical information, cognitive assessment, and amyloid PET scan results were recorded. For visual interpretation, a modified rainbow colormap was created and a regional tau uptake scoring system was proposed to evaluate the degree of tracer uptake and its spatial distribution within five cortical regions. Each region was scored on a scale of [0, 2] as compared to the background, and that resulted in a global scale range of [0, 10]. Four readers interpreted [18F]Florzolotau PET using the visual scale. The global and regional standardized uptake value ratios (SUVr) were also calculated for analysis. Results The result indicates the average global visual scores were 0 ± 0 in the CU group, 3.43 ± 3.35 in the AD-MCI group, and 6.31 ± 2.97 in the AD-D group (p < 0.001). The consensus among the four observers on image scores was high with an intraclass correlation coefficient of 0.880 (95% CI: 0.767–0.936). The average global visual score was significantly associated with global SUVr (r = 0.884, p < 0.0001) and with the CDR-sum of box (r = 0.677, p < 0.0001). Conclusion The visual reading method generated a visual score of [18F]Florzolotau tau-PET with good sensitivity and specificity to identify AD-D or CU individuals from the other patients. The preliminary result also showed that the global visual scores are significantly and reliably correlated with global cortical SUVr, and associated well with the clinical diagnosis and cognitive performance.